Exploring Innovative Thinking Skills Among SME Owners in South Africa: Implications for Business Longevity - (:unkn) unknown (My University, 2024)
Aims: According to the SME South Africa study conducted in 2018, the survival rate of South African Small medium enterprises (SME) is low. The country’s policymakers have become increasingly aware of the need to support the cultivation and growth of resilient, innovative and agile entrepreneurs as can be seen in the National Integrated Small Enterprise Development (NISED) Masterplan. In addition, employees in innovative organizations are more likely to share knowledge to contribute to the improvement of organizational performance, as such environments require high levels of innovative activity. Therefore, the study aimed to assess the level of innovative thinking skills among SME owners in South Africa's construction and manufacturing industries and explore its impact on SME longevity. Study Design: The study employed a descriptive quantitative design, focusing on 204 SME owners from the construction and manufacturing industries in South Africa, selected via quota sampling. Data was collected through an anonymous online questionnaire, which assessed the participants' levels of innovative thinking. The analysis, conducted using Python software, aimed to determine the prevalence of these skills and their implications for the longevity of SMEs. Place and Duration of Study: The study was conducted in South Africa, focusing on the construction and manufacturing industries. The data collection and analysis took place over a period of two years June 2020 and July 2022. Methodology: The study employed a descriptive quantitative approach, using quota sampling to select 204 SME owners from the construction and manufacturing industries in South Africa. Data was gathered through an anonymous online questionnaire and analyzed using Python software to assess innovative thinking levels. Python was selected for descriptive statistics due to its robust and mature libraries like Pandas and NumPy, which facilitate efficient data manipulation and analysis. It ensures co
Keywords: African Research